Clinical case of treatment of acute ischemic stroke (cardioembolic subtype) complicated by aspiration pneumonia and development of acute respiratory distress syndrome - Vaskevich , Anhelina; Chabanovych, Nadiia (The Ukrainian Scientific Medical Youth Journal, 2024)
this clinical case is an example of successful treatment of a patient with acute ischemic stroke in the basin of the middle cerebral artery (cardioembolic subtype), complicated by aspiration of gastric contents and the development of aspiration pneumonia and acute respiratory distress syndrome. After angiographic imaging, the patient urgently underwent endovascular thrombectomy. Neurological examination of the patient showed profound stupor, left-sided hemiparesis, and dysarthria. In 13 hours the postoperative period was complicated by development of Mendelssohn's syndrome and, subsequently, acute respiratory distress syndrome. Complications were treated with mechanical ventilation with high PEEP (positive end-expiratory pressure) for 32 days; empiric antibiotic therapy with the transition to targeted therapy once the bacterial culture and antibioticogram were available, and using low molecular weight heparins. The length of hospital stay was 39 days, the patient was discharged in a clear consciousness, without neurological deficit, 0 points according to the NIHSS (National Institutes of Health Stroke Scale), under the supervision of a surgeon and a cardiologist at the place of residence.